Differences in Characteristics and Outcomes Between Asian and Non-Asian Patients in the TIAregistry.org. Issue 7 (July 2017) - Hoshino, Takao; Uchiyama, Shinichiro; Wong, Lawrence K.S.; Sissani, Leila; Albers, Gregory W.; Bornstein, Natan M.; Caplan, Louis R.; Donnan, Geoffrey A.; Ferro, José M.; Hennerici, Michael G.; Labreuche, Julien; Lavallée, Philippa C.; et al.
Abstract : Background and Purpose—: This study provides the contemporary causes and prognosis of transient ischemic attack (TIA) and minor stroke in Asians and the direct comparisons with non-Asians. Methods—: The TIAregistry.org enrolled 4789 patients (1149 Asians and 3640 non-Asians) with a TIA or minor ischemic stroke within 7 days of onset. Every participating facility had systems dedicated to urgent intervention of TIA/stroke patients by specialists. The primary outcome was a composite of cardiovascular death, nonfatal stroke, and nonfatal acute coronary syndrome. Results—: Approximately 80% of patients were evaluated within 24 hours of symptom onset. At 1 year, there were no differences in the rates of composite cardiovascular events (6.8% versus 6.0%; P =0.38) and stroke (6.0% versus 4.8%; P =0.11) between Asians and non-Asians. Asians had a lower risk of cerebrovascular disease (stroke or TIA) than non-Asians (adjusted hazard ratio, 0.79; 95% confidence interval, 0.63–0.98; P =0.03); the difference was primarily driven by a lower rate of TIA in Asians (4.2% versus 8.3%; P <0.001). Moderately severe bleeding was more frequent in Asians (0.8% versus 0.3%; P =0.02). In multivariable analysis, multiple acute infarcts ( P =0.005) and alcohol consumption ( P =0.02) were independent predictors of stroke recurrence in Asians, whereas intracranial stenosis ( P <0.001), ABCD 2 score ( P <0.001), atrial fibrillation ( P =0.008), extracranial stenosis ( P =0.03), and previous stroke or TIA ( P =0.03) were independent predictors in non-Asians. Conclusions—: The short-term stroke risk after a TIA or minor stroke was lower than expected when urgent evidence-based care was delivered, irrespective of race/ethnicity or region. However, the predictors of stroke were different for Asians and non-Asians. Abstract : Supplemental Digital Content is available in the text.